2021
DOI: 10.1002/humu.24199
|View full text |Cite
|
Sign up to set email alerts
|

More than meets the eye: Expanding and reviewing the clinical and mutational spectrum of brittle cornea syndrome

Abstract: Brittle cornea syndrome (BCS) is a rare autosomal recessive disorder characterized by corneal thinning and fragility, leading to corneal rupture, the main hallmark of this disorder. Non-ocular symptoms include not only hearing loss but also signs of connective tissue fragility, placing it in the Ehlers-Danlos syndrome (EDS) spectrum.It is caused by biallelic pathogenic variants in ZNF469 or PRDM5, which presumably encode transcription factors for extracellular matrix components. We report the clinical and mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 67 publications
0
41
0
Order By: Relevance
“…To assess the possible pathophysiological significance of our data, we analyzed expression of collagen I and V genes in dermal fibroblasts of two BCS patients (P1 and P2) carrying mutations in ZNF469 that both result in a premature termination codon (PTC) (Figure 5c) (Dhooge et al, 2021). No change in ZNF469 expression level was observed in BCS fibroblasts (Figure 5d) indicating that these PTC-containing mRNAs escape non-sense-mediated RNA decay.…”
Section: Znf469 Regulates Expression Of Collagen I Genes With Relevan...mentioning
confidence: 99%
“…To assess the possible pathophysiological significance of our data, we analyzed expression of collagen I and V genes in dermal fibroblasts of two BCS patients (P1 and P2) carrying mutations in ZNF469 that both result in a premature termination codon (PTC) (Figure 5c) (Dhooge et al, 2021). No change in ZNF469 expression level was observed in BCS fibroblasts (Figure 5d) indicating that these PTC-containing mRNAs escape non-sense-mediated RNA decay.…”
Section: Znf469 Regulates Expression Of Collagen I Genes With Relevan...mentioning
confidence: 99%
“…Rupture of the eye globes, either spontaneous or after minor trauma, due to extreme thinning of the cornea is the cardinal feature of brittle cornea syndrome (BCS) and perhaps one of the most debilitating complications within the EDS spectrum [ 12 , 27 ]. It frequently occurs at a young age; however, several adults without ocular rupture have been described.…”
Section: The Clinical Presentation Of Eds An Overviewmentioning
confidence: 99%
“…Hearing loss is a key finding in heritable connective tissue disorders, such as osteogenesis imperfecta and Stickler syndrome but is also present in the majority of individuals with kEDS- FKBP14 or mcEDS and a third of the individuals with BCS [ 7 , 12 , 27 ]. Finally, cryptorchidism is present in the large majority of mcEDS- CHST14 individuals and should raise suspicion of mcEDS in a neonate with signs of connective tissue fragility and contractures [ 7 ].…”
Section: The Clinical Presentation Of Eds An Overviewmentioning
confidence: 99%
“…The role played by ZNF469 in the healthy cornea and in BCS is less clear as the function of the very large protein encoded by this gene is poorly characterised. Since mutations in ZNF469 were first reported to cause BCS (Abu et al, 2008), 30 pathogenic compound heterozygous or homozygous mutations have been identified in the single coding exon of ZNF469 spanning 13 kilobases on chromosome 16q24.2 (Abu et al, 2008;Al-Owain et al, 2012;Christensen et al, 2010;Dhooge et al, 2021;Khan et al, 2012;Khan et al, 2010;Menzel-Severing et al, 2019;Micheal et al, 2019;Ramappa et al, 2014;Rolvien et al, 2020;Skalicka et al, 2020). The majority of these mutations result in premature stop codons that are hypothesised to lead to production of truncated and non-functional protein and are thus considered as loss of function (LOF) mutations.…”
Section: Introductionmentioning
confidence: 99%